Mechanical properties of kenaf fiber reinforced concrete with different water-cement ratio - Mohd Fikree, Badderi (2012)
Kenaf is one of the natural fibers which have many advantages as an alternative reinforcement for fiber reinforced concrete such as low cost, lightweight and high tensile strength. The development in using of kenaf fiber as reinforced in the concrete is a possible forms to improvement the concrete properties. Therefore, this report presents an overview of the developments made in kenaf fiber reinforced concrete (KFRC), in terms of water-cement ratio and mechanical properties. In this study, constant volumes of kenaf fiber are used and difference water-cement ratio (w/c) in concrete to be main focus. This study concentrated on the compressive strength, flexural strength and splitting tensile strength of KFRC compared to conventional concrete. All of the specimens were conducted in different w/c ratio (0.5, 0.6 and 0.7) and cured in water for 7, 14 and 28 days. The result determined that compressive and flexural strength of KFRC are lower than conventional concrete. Meanwhile, the KFRC splitting tensile strength is higher than conventional concrete. This is shows that addition of kenaf fiber is not contributing increase the strengths. The result also determined that strengths of the KFRC are decreasing with increasing w/c ratio. As a conclusion, w/c ratio is significantly affecting the concrete strengths.